2019
DOI: 10.15171/joddd.2019.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of incorporation of silver and titanium nanoparticles on feldspathic ceramic toughness

Abstract: Background. Porcelain is brittle and in many situations it requires replacement in fractured or chipped restorations. The prospects exist in improving the strength of feldspathic porcelain to widen its applications. This study evaluated the fracture toughness of feldspathic porcelain after incorporation of silver and titanium nanoparticles at varying concentrations (0.5 wt%, 1 wt%, 1.5 wt% and 2 wt%). Methods. Test specimen dimensions were standardized to ASTM C1421–16 standards and a three-point flexure test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…(22)(23)(24) In this study, flexural strength results were in accordance with De la Fuente et al (2016) (25) , and Karthikeyan et al (2019). (26) They recorded an increase in fracture toughness of sintered porcelain due to the incorporation of silver nanoparticles . They reported that porcelain toughening occurred due to the incorporation of fine metal particles in the porcelain matrix and explained how the lamella structures hold the fracture surfaces together after (1196) the crack propagation through the porcelain matrix and that microcracks and cracks form around the main crack resulting in stress relieve at the crack tip.…”
Section: Discussionmentioning
confidence: 99%
“…(22)(23)(24) In this study, flexural strength results were in accordance with De la Fuente et al (2016) (25) , and Karthikeyan et al (2019). (26) They recorded an increase in fracture toughness of sintered porcelain due to the incorporation of silver nanoparticles . They reported that porcelain toughening occurred due to the incorporation of fine metal particles in the porcelain matrix and explained how the lamella structures hold the fracture surfaces together after (1196) the crack propagation through the porcelain matrix and that microcracks and cracks form around the main crack resulting in stress relieve at the crack tip.…”
Section: Discussionmentioning
confidence: 99%
“…However, this processing method adversely may affect the color of the feldspar porcelain, and the concentration of nanoparticles should not be too high. High concentrations of silver and titanium nanoparticles will reduce the fracture resistance of the feldspar porcelain [ 19 ].…”
Section: Silicate Ceramicsmentioning
confidence: 99%
“…As dental porcelain provides excellent esthetic results, simulating natural teeth, it has been widely used as a fixed dental prosthesis material, but it has functional limitations as chipping or fracture due to its strength. The improvement of strength through the advancement of technology and newer available nanomaterials to broaden their applications is the scope [12].…”
Section: Since 2002mentioning
confidence: 99%
“…Porcelain materials were reinforced with other materials such as leucite crystals and fibers in the earlier years to nanoparticles in recent days to enhance the mechanical properties [12]. The use of nanoparticles has become a significant area of research in dentistry, the main use has been focused in increasing the mechanical properties such as surface hardness, ductility, and toughness.…”
Section: Since 2002mentioning
confidence: 99%